Volumetric sphygmography with assessment of arterial stiffness as an alternative to ultrasound examination of the carotid arteries in the cardiovascular risk stratification - A. R. Zairova; A. N. Rogoza; E. V. Oshchepkova; S. A. Shalnova; I. A. Trubacheva; V. S. Kaveshnikov; S. A. Boytsov (Кардиоваскулярная терапия и профилактика)
Aim. To study the potential of volume sphygmography (VS) with assessment of arterial stiffness (AS) as an alternative to carotid ultrasound in cardiovascular risk (CVR) stratification in a Tomsk adult population sample.Material and methods. The results of a survey of a Tomsk population sample aged 40 to 64 years (n=971) were analyzed. They underwent carotid ultrasound and VS with cardio-ankle vascular index (CAVI) assessment as part of the ESSE-RF study. During a 5-year follow-up, cardiovascular events (CVEs) (cardiovascular death, non-fatal myocardial infarction (MI) or stroke) were registered in 34 people. Individuals with high and very high CVR were identified according to traditional CVR stratification based on clinical, anamnestic, and carotid ultrasound data. Alternative options for CVR stratification using the criterion of increased AS (CAVI ≥8) were considered. The effectiveness of CVR stratification was assessed by identifying CVR over a 5-year follow-up period.Results. Based on clinical, anamnestic and carotid ultrasound (plaques in 40% (n=386)) data, 605 (62%) individuals were classified as high and very high risk, accounting for 88% (30 out of 34) of CVEs over the follow-up period (CVE rate over 5 years — 5%). CAVI ≥8 was detected in 45% (n=432) of those examined. When using the CAVI ≥8 indicator instead of the plaque criterion, a group of 633 people was formed, which also accounted for 88% (30 out of 34) of the CVEs (CVE rate over follow-up period — 4,7%), i.e. the results are comparable with the traditional approach.Conclusion. When stratifying the CVR in the Tomsk population sample, consideration of the criterion of increased AS (CAVI ≥8) in addition to clinical and anamnestic data forms a group of people with a comparable CVE rate over a 5-year follow-up period, as when taking into account the plaque criterion according to carotid ultrasound, which account for the same number (88%) of the CVEs. This suggests the use of VS with AS assessment in the CVR stratification.